Drosophila CG3303 is an essential endoribonuclease linked to TDP-43-mediated neurodegeneration - Laneve, Pietro (Sci Rep, 2017)
Endoribonucleases participate in almost every step of eukaryotic RNA metabolism, acting either as degradative or biosynthetic enzymes. We previously identified the founding member of the Eukaryotic EndoU ribonuclease family, whose components display unique biochemical features and are flexibly involved in important biological processes, such as ribosome biogenesis, tumorigenesis and viral replication. Here we report the discovery of the CG3303 gene product, which we named DendoU, as a novel family member in Drosophila. Functional characterisation revealed that DendoU is essential for Drosophila viability and nervous system activity. Pan-neuronal silencing of dendoU resulted in fly immature phenotypes, highly reduced lifespan and dramatic motor performance defects. Neuron-subtype selective silencing showed that DendoU is particularly important in cholinergic circuits. At the molecular level, we unveiled that DendoU is a positive regulator of the neurodegeneration-associated protein dTDP-43, whose downregulation recapitulates the ensemble of dendoU-dependent phenotypes. This interdisciplinary work, which comprehends in silico, in vitro and in vivo studies, unveils a relevant role for DendoU in Drosophila nervous system physio-pathology and highlights that DendoU-mediated neurotoxicity is, at least in part, contributed by dTDP-43 loss-of-function.